Where in the World? Adult Educator Learning and Professional Development Leading Study Abroad Programs - Joellen E Coryell; Cheri hatcher (Adult Education Research Conference, 2022)
In this summary of on-going research, we discuss our investigation about adult educator motivations and professional development to lead study abroad programs for adults.
Keywords: adult study abroad; international adult and higher education; faculty professional development; international teaching